Effect of black cumin (Nigella sativa) on heart rate, some hematological values, and pancreatic ?-cell damage in cadmium-treated rats - Demir, Halit; Kanter, Mehmet; Coskun, Omer; Uz, Yesim Hulya; Koc, Ahmet; Yildiz, Abdulmelik (Humana Press Inc, 2006)
This study was designed to investigate the effect of Nigella saliva (NS) on the heart rate, some hematological values, and pancreatic beta-cell damage in cadmium (Cd)-treated rats. The rats were randomly grouped into one of three experimental groups: Control, Cd treated, and Cd + NS treated. Each group contained 10 animals. The Cd-treated and Cd + NS-treated groups were injected subcutaneously daily with CdCl2 dissolved in isotonic NaCl in the amount of 2 mL/kg for 30 d, resulting in a dosage of 0.49 mg Cd/kg/d. The control group was injected with only isotonic NaCl (2 mL/kg/d) throughout the experiment (for 30 d). Three days prior to administration of CdCl2, the Cd + NS-treated group received the daily intraperitoneal (ip) injection of 2 mL/kg NS until the end of the study; animals in all three groups were fasted for 12 h and blood samples were taken for the determination of the glucose and insulin levels, red blood cell (RBC) and white blood cell (WBC) counts, packet cell volume (PCV), and hemoglobin (Hb) concentration. The heart rates of rats were also measured by a direct writing electrocardiograph before the blood withdrawals. It was found that NS treatment increased the lowered insulin levels, RBC and WBC counts, PCV, and neutrophil percentage in Cd-treated rats. However, the WBC count of Cd-treated rats with NS treatment was still lower than those of control values. NS treatment also decreased the elevated heart rate and glucose concentration of Cd-treated rats. Pancreatic tissues were also harvested from the sacrificed animals for morphological and immunohistochemical examinations. Cd exposure alone caused a degeneration, necrosis, and weak degranulation in the beta-cells of the pancreatic islets. In Cd + NS-treated rats, increased staining of insulin and preservation of islet cells were apparent. It is concluded that NS treatment might decrease the Cd-treated disturbances on heart rate, some hematological values, and pancreatic beta-cell.
Keywords: Nigella sativa; cadmium; heart rate; hematological values; pancreatic beta-cell; rat